TINGKAT KEPUASAN NASABAH TERHADAP STANDAR PELAYANAN (STUDI KASUS PADA PT. BANK X DI PALEMBANG) - Lidyah, Rika; Anggraini, Sherly (Nurani, 2014)
Abstract: Service is a process of assistance to others in certain ways that require sensitivity and interpersonal relationships in order to create satisfaction and success. Satisfaction is feeling happy or disappointed someone who comes after comparing the performance (results) is thinking of product performance (results) are expected. The purpose of this study is the first, to find out what factors affect the level of customer satisfaction with standards of service at PT. Bank X Palembang, and second, to find out what factors affect the level of customer satisfaction with standards of service at PT Bank X Palembang. The sample was taken is the customers who have experienced the service at PT. Bank X Palembang obtained a sample of 47 respondents. This sample was taken by way of non-probability sampling with Accidental sampling techniques. The results showed, first, the analysis of two pairs hypothesis test (different tests) show that there is a difference between the performance perceived by the customer expectations of service standards at PT. Bank X Palembang, this shows the bank's performance is still not fully meet customer expectations. Second, factors that affect the highest customer satisfaction level of service standards at PT. Bank X Palembang ie employees to be friendly and polite registration. ملخص :الخدمة هي عملية لتقديم المساعدة إلى الآخرين بطرق معينة تتطلب حساسية والعلاقات بين الأشخاص من أجل خلق الارتياح والنجاح. الارتياح هو الشعور بالسعادة أو بخيبة الأمل لشخص يأتي بعد مقارنة الأداء (النتائج) هو التفكير في أداء المنتج (النتائج) من المتوقع. والغرض من هذه الدراسة هي الأولى ، لمعرفة ما هي العوامل التي تؤثر في مستوى رضا العملاء مع معايير الخدمة في حزب العمال. البنك باليمبانج العاشر ، والثاني ، لمعرفة ما هي العوامل التي تؤثر في مستوى رضا العملاء مع معايير الخدمة في حزب العمال. البنك العاشر باليمبانج. وكانت العينة التي اتخذت هي العملاء الذين لديهم خبرة في الخدمة في حزب العمال. البنك العاشر باليمبانج الحصول على عينة من 47 المستجيبين. هذه عينة أخذت من طريق غير احتمال أخذ العينات مع تقنيات أخذ العينات العرضي. وأظهرت النتائج ، أولا ، تحليل اثنين من أزواج اختبار الفرضية (اختبارات مختلفة) تبين أن هناك فرقا بين الأداء ينظر إليه من جانب توقعات العملاء من معايير الخدمة في حزب العمال. البنك باليمبانج العاشر ، وهذا يدل على أداء البنك لا تزال غير كاملة تلبية توقعات العملاء. ثانيا ، العوامل التي تؤثر على أعلى مستويات رضا العملاء من معايير الخدمة في حزب العمال. البنك العاشر باليمبانج الموظفين أي أن تكون ودية ومهذبة للتسجيل. Kata Kunci: kepuasan, pelayanan, persepsi, bank.